"Vamos sair da crise": um Debate com Ignácio M. Rangel e Luiz Carlos Bresser Pereira' - Luiz Carlos Bresser (Geosul)
"Vamos sair da crise": um Debate com Ignácio M. Rangel e Luiz Carlos Bresser Pereira'